Thought in the Act : Passages in the Ecology of Experience - Manning, Erin; Massumi, Brian (University of Minnesota Press, 2014)
""Every practice is a mode of thought, already in the act. To dance: a thinking in movement. To paint: a thinking through color. To perceive in the everyday: a thinking of the world's varied ways of affording itself."--Thought in the Act Combining philosophy and aesthetics, Thought in the Act is a unique exploration of creative practice as a form of thinking. Challenging the common opposition between the conceptual and the aesthetic, Erin Manning and Brian Massumi "think through" a wide range of creative practices in the process of their making, revealing how thinking and artfulness are intimately, creatively, and inseparably intertwined. They rediscover this intertwining at the heart of everyday perception and investigate its potential for new forms of activism at the crossroads of politics and art. Emerging from active collaborations, the book analyzes the experiential work of the architects and conceptual artists Arakawa and Gins, the improvisational choreographic techniques of William Forsythe, the recent painting practice of Bracha Ettinger, as well as autistic writers' self-descriptions of their perceptual world and the experimental event making of the SenseLab collective. Drawing from the idiosyncratic vocabularies of each creative practice, and building on the vocabulary of process philosophy, the book reactivates rather than merely describes the artistic processes it examines. The result is a thinking-with and a writing-in-collaboration-with these processes and a demonstration of how philosophy co-composes with the act in the making. Thought in the Act goes beyond proposing to enact a collaborative mode of thinking in the act at the intersection of art, philosophy, and politics."--